PERAN IBU DALAM MENGEMBANGKAN PENGUASAAN PERILAKU ADAPTIF ANAK TUNAGRAHITA - Leonita Dwi Agustin; Yapina Widyawati (MANASA, 2012)
Mastery of adaptive behavior is the important skill to be achieved by the children with mental retardation One of the indicator for a child to be called mental retarded is the lack of his adaptive behavior ability. Eventhough, adaptive behavior is very important to be mastered by mental retarded children in surviving their lives. This reason makes adaptive behavior becomes a focus for this research. In mastering the adaptive behavior, the role of a mother is very neeeded. This is related to Indonesian culture, while father is breadwinner and mother is nurturing their children. The role of mother focused on the role as a teacher, as a managing behavior, relating to the school, counselors, and educating significant other. Data obtained though observation and intervews with three mothers who have children with mental retardation that entered elementary school. Result of the study showed that as a teacher, mother showed the adaptive behavior and asked the children to do as so independently. As a behavior manager, mothers gave reward and punishment to their children. As a relationship builder with school, mothers didin’t actively involved in school activities. As conselor, mothers helped their children to solve socialization problems. The role in educating significant other did not occur because they do the parenting on their own without any help.